2022
DOI: 10.3389/fpsyg.2021.695241
|View full text |Cite
|
Sign up to set email alerts
|

Applying Social Cognitive Theory in Predicting Physical Activity Among Chinese Adolescents: A Cross-Sectional Study With Multigroup Structural Equation Model

Abstract: This cross-sectional study aimed to assess the applicability of social cognitive determinants among the Chinese adolescents and examine whether the predictability of the social cognitive theory (SCT) model on physical activity (PA) differs across gender (boys and girls) and urbanization (urban and suburban). A total of 3,000 Chinese adolescents ranging between the ages of 12–15 years were randomly selected to complete a set of questionnaires. Structural equation modeling (SEM) was applied to investigate the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 73 publications
1
6
0
Order By: Relevance
“…Subgroup analysis revealed that interventions based on SDT significantly increased TPA and MVPA in children and adolescents, while interventions based on SCT significantly reduced SB in this population. Previous studies have consistently shown that interventions based on SCT effectively improve PA among adolescents, which aligns with the findings of this study [ 54 ]. SCT is commonly used to elucidate the mechanisms underlying the improvement in PA through behavior change interventions.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Subgroup analysis revealed that interventions based on SDT significantly increased TPA and MVPA in children and adolescents, while interventions based on SCT significantly reduced SB in this population. Previous studies have consistently shown that interventions based on SCT effectively improve PA among adolescents, which aligns with the findings of this study [ 54 ]. SCT is commonly used to elucidate the mechanisms underlying the improvement in PA through behavior change interventions.…”
Section: Discussionsupporting
confidence: 92%
“…Currently, mHealth app interventions employ multiple types of BCT that have been shown to be effective in influencing intervention outcomes [21]. Eight out of the 28 included studies did not employ theoretical frameworks in their mHealth app interventions [31,36,37,45,47,49,50,52] [65]. SCT is commonly used to elucidate the mechanisms underlying the improvement in PA through behavior change interventions.…”
Section: Theoretical Paradigmmentioning
confidence: 99%
“…Finally, 243 (203 boys, 40 girls, age: 20.56 ± 1.51 years) participants completed the second-wave data collection at the 3-month follow-up in December 2021. Based on the common rule of thumb for estimating the sample size for a structural equation modeling (SEM) (i.e., the sample size is usually 10 times the number of variables) [ 35 , 36 ], the sample size of 243 was sufficient for this study. All participants were informed about the study purpose and signed the written informed consent form before the data collection.…”
Section: Methodsmentioning
confidence: 99%
“…More specifically, an individual's evaluation of these factors can contribute to them establishing goals or standard expectations, which subsequently drive behavioral choices. SCT has been applied successfully in past work within the context of fitness and health (e.g., Marmo, 2013;Liu et al, 2022) and more recently, WHT and broader mHealth initiatives (Lee and Cho, 2017;Lin and Chang, 2018;Gowin et al, 2019). In each case, both personal and environmental factors have been identified as driving engagement.…”
Section: Theoretical Frameworkmentioning
confidence: 99%